Role of gender, family, lifestyle and psychological factors in self-rated health among urban adolescents in Peru: a school-based cross-sectional survey. Issue 2 (3rd February 2016) - Sharma, Bimala; Nam, Eun Woo; Kim, Dohyeong; Yoon, Young Min; Kim, Yeunju; Kim, Ha Yun
Abstract : Objective: We examined the role of gender, family, lifestyle and psychological factors in self-rated health. Design: Cross-sectional study. Setting: A total of 970 randomly selected students from 11 secondary schools in Lima and Callao, Peru, participated in 2014. Main outcome measure: Self-rated health was measured with a single item: 'In general, how would you rate your health?' Responses were arranged along a five-point Likert-type scale: 'excellent', 'very good', 'good', 'fair' and 'poor'. The outcome variable was dichotomised as 'good' (excellent, very good or good) or 'poor/fair' (poor or fair). Methods: We calculated adjusted ORs (AORs) and 95% CIs for poor/fair self-rated health using multivariate logistic regression analyses at 3-graded levels. Results: 32.5% of the respondents had fair/poor self-rated health, 23.7% of the total males and 40.0% of the total female samples. Males were less likely to have poor/fair self-rated health (AOR 0.61; CI 0.41 to 0.91). Poor family support strongly increased the likelihood of having poor/fair self-rated health (no support, (AOR 3.15; CI 1.63 to 6.09); low support, (AOR 2.50; CI 1.29 to 4.85)). The other associated variables were missed meals due to a shortage of food (AOR 1.97; CI 1.15 to 3.36), television watching during leisure time (AOR 1.70; CI 1.09 to 2.67), low physical activity (AOR 1.49; CI 1.03 to 2.15), school absenteeism (AOR 1.54; CI 1.03 to 2.31) and perceived life satisfaction (AOR 0.28; CI 0.15 to 0.25). Conclusions: Gender, missing meals due to a shortage of food, family support, physical activity and life satisfaction influenced self-rated health among adolescents in Peru. Interventions that focus on promoting physical activity for at least 1 h each day for 3 or more days per week, food security and strengthening supportive family roles may improve self-rated health during adolescence.